Hypercalcemia After Cosmetic Oil Injections: Unraveling Etiology, Pathogenesis, and Severity. (13th October 2020) - Eldrup, Ebbe; Theilade, Simone; Lorenzen, Mette; Andreassen, Christine H; Poulsen, Katrine H; Nielsen, John E; Hansen, Ditte; El Fassi, Daniel; Berg, Jais O; Bagi, Per; Jørgensen, Anne; Blomberg Jensen, Martin
ABSTRACT: Intramuscular injections of paraffin oil can cause foreign body granuloma formation and hypercalcemia. Macrophages with the ability to produce high levels of 1, 25(OH)2 D3 may induce the mineral disturbance, but no major series of patients have been published to date. Here, medical history, physical evaluation, biochemical, and urinary analysis for calcium homeostasis were obtained from 88 males, who 6 years previously had injected paraffin or synthol oil into skeletal muscle. Moreover, granuloma tissue from three men was cultured for 48 hours ex vivo to determine 1, 25(OH)2 D3 production supported by qPCR and immunohistochemistry of vitamin D metabolism and immune cell populations after treatment with 14 different drugs. The 88 men were stratified into men with hypercalcemia (34%), whereas normocalcemic men were separated into men with either normal (42%) or suppressed parathyroid hormone (PTH) (24%). All men had high calcium excretion, and nephrolithiasis was found in 48% of hypercalcemic men, 22% of normocalcemic men with normal PTH, and 47% of normocalcemic men with suppressed PTH. Risk factors for developing hypercalcemia were oil volume injected, injection of heated oil, high serum interleukin‐2 receptor levels, and high urine calcium. High 1, 25(OH)2 D3 /25OHD ratio, calcium excretion, and low PTH was associated with nephrolithiasis. The vitamin D activating enzyme CYP27B1 was markedly expressed in granuloma tissue, and 1, 25(OH)2 D3 was released in concentrations corresponding to 40% to 50% of the production by human kidney specimens. Dexamethasone, ketoconazole, and ciclosporin significantly suppressed granulomatous production of 1, 25(OH)2 D3 . In conclusion, this study shows that injection of large oil volumes alters calcium homeostasis and increases the risk of nephrolithiasis. Hypercalciuria is an early sign of disease, and high granulomatous 1, 25(OH)2 D3 production is part of the cause. Prospective clinical trials are needed to determine if ciclosporin, ketoconazole, or other drugs can be used as prednisolone‐sparing treatment. © 2020 American Society for Bone and Mineral Research (ASBMR).